2023
DOI: 10.3390/cells12121609
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1’s Role in Preventing Alloreactive T Cell Responses Following Hematopoietic and Organ Transplant

Shane Handelsman,
Juliana Overbey,
Kevin Chen
et al.

Abstract: Over the past decade, Programmed Death-Ligand 1 (PD-L1) has emerged as a prominent target for cancer immunotherapies. However, its potential as an immunosuppressive therapy has been limited. In this review, we present the immunological basis of graft rejection and graft-versus-host disease (GVHD), followed by a summary of biologically relevant molecular interactions of both PD-L1 and Programmed Cell Death Protein 1 (PD-1). Finally, we present a translational perspective on how PD-L1 can interrupt alloreactive-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 143 publications
(195 reference statements)
0
5
0
Order By: Relevance
“…Utilizing PD-L1 as an immunomodulatory approach presents a potential strategy for preventing graft-versus-host disease (GVHD) as well as preventing transplant rejection. However, the function of this pathway in a clinical context remains to be precisely determined [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Utilizing PD-L1 as an immunomodulatory approach presents a potential strategy for preventing graft-versus-host disease (GVHD) as well as preventing transplant rejection. However, the function of this pathway in a clinical context remains to be precisely determined [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of tumor frequently arises as a complication in patients who are chronically immunosuppressed following a transplant. Cemiplimab represents a promising therapeutic option that can be incorporated into the treatment regimen for transplant patients requiring ongoing immunosuppression who develop this type of skin malignancy [ 87 , 158 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amarnath et al (213) found that Tregs could promote the generation of bone marrow DCs and reduce their ability to stimulate the generation of efficient T cells in GvHD. Tregs have high surface expression levels of PD-L1, which can bind to PD-L1 of DCs, thus inhibiting the activation of T cells and alleviating GvHD (214,215). In addition, Tregs can express inhibitory molecules (e.g.…”
Section: Transplantationmentioning
confidence: 99%